2020
DOI: 10.3390/su12104252
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Waste or Capturing Innovation? Comparing Self-Organising Potentials of Surplus Food Redistribution Initiatives to Prevent Food Waste

Abstract: The context for this article is the rapid international growth of (surplus) food redistribution initiatives. These are frequently reliant on networks of volunteer labour, often coordinated by digital means. Movements with these characteristics are increasingly viewed by researchers, policymakers and practitioners as cases of self-organisation. The article explores the nature and extent of self-organisation in food redistribution initiatives. Two contrasting UK initiatives were studied using ethnographic method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Value-added preparation includes social enterprises that use SF as a raw material to make new products. An example of this is Toast Ale in England, a beer made using surplus bread in place of virgin barley, with profits donated to charities [76]; another example is RecuperAle in Italy, which uses the same method, but involves detainees in the production [77]. A similar method is used to make many other products (jams, chutneys, juices, etc.).…”
Section: Human Reusementioning
confidence: 99%
“…Value-added preparation includes social enterprises that use SF as a raw material to make new products. An example of this is Toast Ale in England, a beer made using surplus bread in place of virgin barley, with profits donated to charities [76]; another example is RecuperAle in Italy, which uses the same method, but involves detainees in the production [77]. A similar method is used to make many other products (jams, chutneys, juices, etc.).…”
Section: Human Reusementioning
confidence: 99%
“…A study (Spring & Biddulph, 2020) has identified the rapid global growth of surplus food redistribution initiatives relying on volunteer activities mediated by ICT-based platforms. The involvements and contributions of cultures, organisational facts and internal experiences has also been explored by another study (Rut, Davies, & Ng, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, FLW and obesity are rising in EU and, simultaneously, 33 million people cannot afford a quality meal every second day making food assistance indispensable in several Member States. Many initiatives have emerged to mitigate FLW [ 13 ] but a balance between decrease food waste and requirements of food safety should be also considered in designing such initiatives [ 14 ], thus generating a “win-win” situation for both food and nutrition safety and environmental sustainability [ 1 ].…”
Section: Introductionmentioning
confidence: 99%